2012
DOI: 10.1177/0010414012453034
|View full text |Cite
|
Sign up to set email alerts
|

Economic Development Strategies and Communal Violence in Africa

Abstract: This article explores the relationship between economic development strategies and conflict outcomes in Africa, using a comparison of Côte d’Ivoire and Ghana. Findings suggest that development strategies that create contestation for resources along identity group lines, absent provisions for co-opting disenfranchised groups, increase the likelihood of communal violence, whereas development plans that transcend ascriptive social identities bear the greatest chance of generating long-term peace, irrespective of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Poor economic conditions and poverty are precisely the causes of majority of conflicts (Lee 2011). Therefore, economic reconstruction of the country or the region should be the priority once the conflict ends (Lemmon 2012 andMcCauley 2013). It was found that that creating a peace and prosperity in areas of conflict zones includes business which generate economic and social value, which directly contribute to building of community and overall recovery (Kolk and Lenfant, 2016).…”
Section: Literature Review and Research Issuesmentioning
confidence: 99%
“…Poor economic conditions and poverty are precisely the causes of majority of conflicts (Lee 2011). Therefore, economic reconstruction of the country or the region should be the priority once the conflict ends (Lemmon 2012 andMcCauley 2013). It was found that that creating a peace and prosperity in areas of conflict zones includes business which generate economic and social value, which directly contribute to building of community and overall recovery (Kolk and Lenfant, 2016).…”
Section: Literature Review and Research Issuesmentioning
confidence: 99%
“…The northern regions were neglected during the economic boom and the promised development never materialized during the economic downturn in the 1980s. In Ghana the plan was to subdue subnational tensions and in turn avoid conflict and increase human security by growing the economy nationally rather than regionally (McCauley, 2012).…”
Section: Wave Two: Economic Imperialismmentioning
confidence: 99%
“…On one hand national economic development plans tend to be based on short to medium term goals. They are developed by a particular political party government in power based on what they consider to be key priorities (McCauley, 2013;Arku, 2006). On the other hand, tourism development plans tend to be long term policy documents that more often than not outlive the duration of any one political party government (Hall, 2008).…”
Section: Introductionmentioning
confidence: 99%